Preparation of Zinc Sulfide Microspheres and Its Photocatalytic Activity on Antibiotics - Hao, Donggang; Zhang, Xiaojie; Ying, Weiyong; Li, Tao (Asian Journal of Chemistry, 2012)
In this work, the zinc sulfide microspheres were prepared by hydrothermal synthesis method in the presence of polyvinylpyrrolidone as surfactants. The as-prepared zinc sulfide microspheres were characterized by X-ray diffraction, scanning electron microscopy, UV-VIS diffuse reflectance spectra and Fourier transform infrared. The results showed that the size of prepared particles uniform and dispersed well. The decgradation rate of the antibiotics pollutants ciprofloxacin and gatifloxacin were studied under UV and visible light irradiation. The photocatalytic experiments showed that the degradation rate of ciprofloxacin and gatifloxacin with the as-prepared zinc sulfidephotocatalysts were 75.31 % and 74.57 % under UV light irradiation 60 min, respectively. However,the degradation rate of ciprofloxacin and gatifloxacin are very low in the visible light.